KEPEDULIAN LINGKUNGAN SISWA DITINJAU DARI ASPEK PENGETAHUAN TENTANG KONSEP DASAR EKOLOGI DAN GENDER - Suhardin Suhardin (Program Studi Pendidikan Kependudukan dan Lingkungan Hidup, 2017)
The objective of this research is to know the diffrences of environmental concern as well as to find out the relionship between basic concept of ecology knowledge with environmental concern among male and female students. The Comparative Analysis was conducted in SMA Depok involving 96 students chosen by using purposive random sampling.The data analysis and interpretation indicated that: 1. There is significant correlation in students basic concepts of ecology knowledge between with the environmental concerns, 2. There is verry significant difference students among male and female environmental concerns 3. There is significant correlation in male students basic concepts of ecology knowledge between with the environmental concerns, 4. There is significant correlation in female students basic concepts of ecology knowledge between with the environmental concerns.